Chemometrics-assisted cyclodextrin-enhanced excitation-emission fluorescence spectroscopy for the simultaneous green determination of bisphenol A and nonylphenol in plastics - Pellegrino Vidal, Rocio (2015)
Abstract The aim of this work was to quantify two relevant priority chemicals, bisphenol A (BPA) and 4-nonylphenol (NP), coupling the sensitivity of fluorescence in organized media and the selectivity of multivariate calibration, measuring excitation-emission fluorescence matrices in an aqueous methyl-β-cyclodextrin solution. The studied priority pollutants are two of the most frequently found xenoestrogens in the environment, and are therefore of public health concern.The data were successfully processed by applying unfolded partial least-squares coupled to residual bilinearization (U-PLS/RBL), which provided the required selectivity for overcoming the severe spectral overlapping among the analyte spectra and also those for the interferents present in real samples. A rigorous International Union of Pure and Applied Chemistry (IUPAC)-consistent approach was applied for the calculation of the limits of detection. Values in the ranges of 1-2 and 4-14 ng mL-1 were obtained in validation samples for BPA and NP, respectively. On the other hand, low relative prediction errors between 3% and 8% were achieved. The proposed method was successfully applied to the determination of BPA and NP in different plastics. In positive samples, after an easy treatment with a small volume of ethanol at 35°C, concentrations were found to range from 26 to 199 ng g-1 for BPA, and from 95 to 30,000 ng g-1 for NP.